2018
DOI: 10.2147/ott.s187315
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol induces ubiquitin-dependent degradation of mTOR in breast cancer cells

Abstract: BackgroundCelastrol is a major active component of the thunder god vine (Tripterygium wilfordii) used in traditional Chinese medicine to treat chronic inflammatory and autoimmune diseases. Celastrol inhibits PI3K–Akt–mTOR signaling, which is frequently dysregulated in tumors and critical for tumor-cell proliferation and survival, but the underlying mechanisms are still not fully understood. In the present study, we investigated detailed mechanisms of celastrol inhibition of mTOR signaling in breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The purity of celastrol (Sigma) was ≥98% and it was dissolved in DMSO (Sigma). Cells were incubated with various doses of celastrol (0.1, 0.5, 1, 2, and 5 μM) for 24 h based on methods described in previous reports [ 6 , 15 ]. The high doses (2 and 5 μM) and low doses (0.1, 0.5, and 1 μM) of celastrol were differentiated according to the influence on cell viability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purity of celastrol (Sigma) was ≥98% and it was dissolved in DMSO (Sigma). Cells were incubated with various doses of celastrol (0.1, 0.5, 1, 2, and 5 μM) for 24 h based on methods described in previous reports [ 6 , 15 ]. The high doses (2 and 5 μM) and low doses (0.1, 0.5, and 1 μM) of celastrol were differentiated according to the influence on cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…Celastrol has been reported to play anti-cancer roles and may be a potential therapeutic candidate in breast cancer. For example, Li et al reported that celastrol inhibits breast cancer cell growth by suppressing the mTOR pathway in vitro and in vivo [ 6 ]. Jang et al showed celastrol suppresses growth of breast cancer cells by regulating estrogen receptor α [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CEL is a plant-derived triterpenoid and has anticancer effect against a wide variety of cancers ( Li et al, 2018 , 2019 ; Jiang et al, 2019 ). It can induce apoptosis of vincristine-multidrug-resistant oral cancer cells via JNK1/2 signaling pathway ( Lin et al, 2019 ).…”
Section: The Isolation and Application Of Exosomes In The Delivery Ofmentioning
confidence: 99%
“…Furthermore, celastrol can induce cell‐cycle arrest at the G0/G1 phase, which is a novel effect based on thiol‐related Hsp90 inhibition 5,31 . Later, Li et al 113 observed that celastrol is an inhibitor of mTOR, which could disturb its association with Hsp90 while conversely enhancing its interaction with Cdc37.…”
Section: Bioactivity and Mechanisms Of Action Of Celastrolmentioning
confidence: 99%